Trends in SARS-CoV-2-related pediatric hospitalizations reported to the Canadian Nosocomial Infection Surveillance Program, March 2020 to December 2022 - Diane Lee; Erin McGill; Linda Pelude; Robyn Mitchell; Jeannette L. Comeau; Charles Frenette; Bonita E Lee; Marie-Astrid Lefebvre; Jocelyn A. Srigley; Nisha Thampi (Cambridge University Press, 2024)
Abstract Objective: This study describes trends in COVID-19 hospitalizations and healthcare-associated (HA) COVID-19 in Canada among pediatric (age <18 years) patients during pre-Omicron and Omicron-dominant periods. Design: Prospective surveillance for COVID-19 infection Setting: The Canadian Nosocomial Infection Surveillance Program is a sentinel surveillance system with 45 hospitals providing COVID-19 data on pediatric patients, including all 13 pediatric tertiary care facilities in Canada. Patients: Pediatric patients hospitalized with laboratory-confirmed COVID-19 at a participating hospital between March 1, 2020, and December 31, 2022. Methods: Analyzed case-level data on pediatric patients with COVID-19, including demographics, acquisition source, and outcomes. Results: Among 5,143 pediatric cases, the majority (81%) were reported during the Omicron-dominant period (beginning December 26, 2021). However, a lower proportion required intensive care during the Omicron wave (11% vs 14%, P < 0.05); no difference in mortality was observed. Of those patients admitted to hospital due to COVID-19 (n = 2,700), 45% had at least one pre-existing comorbidity. The majority (90%) of patients with HA-COVID-19 were reported during the Omicron period. There was no difference in mortality between patients with HA and community-associated (CA) infection, although a greater proportion of CA infections led to intensive care unit admission (6% vs 13%, P < 0.01). Conclusions: Surveillance findings indicate that both HA- and CA-COVID-19 hospitalizations in Canada increased among pediatric patients following the emergence of the Omicron variant, although disease severity decreased. Pre-existing health conditions were common among pediatric patients hospitalized with COVID-19, highlighting the importance of preventing severe illness in this sub-population.